Fatores políticos e logísticos da reestruturação territorial de Ponta Grossa (PR): a viabilidade do CLIA – Centro Logístico Aduaneiro e o Aeroporto Internacional de Cargas de Tibagi. - Nascimento, Sueli Aparecida do (2010)
This paper analyzes the political and logistical factors of the implementation of new fixed spatial region of Campos Gerais, Paraná, notably the CLIA (Logistics Center Industrial Customs) and the International Airport Charges Tibagi. For this, the theoretical part of understanding the evolution of capitalism and its phases, reflected in public policy and logistical differentiated. The National Integration (IIRSA) is analyzed in its potential to transform restructured the logistics of the Campos Gerais region, which promise to be effective from the implementation of projects under study. It also examined the regional flow and its potential to justify the scale of geographic objects in the context of the announced restructuring designed by IIRSA. The movement of deterritorialization - (re) territorialization from the incorporation in the territory of such infrastructure may also lead to new processes of socio-territorial selectivity, arising out of new networks and systems planned, and new dynamic traffic flow requirements seconds globalized market economy.